Análise temporal e espacial dos óbitos por pré-eclâmpsia: cenário nacional e cearense no período de 2009 a 2020 - Freire, Bárbara Gomes Santos (2022)
Preeclâmpsia is a hypertensive syndrome responsible for high rates of maternal morbidity and mortality at a national and global level, population-based studies on the disease are incipient in Brazil. The objective was to analyze the spatial distribution of deaths from preeclampsia in Brazil and Ceará from 2009 to 2020. This is an ecological study. The population consisted of all records of deaths from preeclâmpsia in Brazil and in the state of Ceará, from 2009 to 2020. The information used is in the public domain. Data on deaths were obtained from the Information System on Mortality of the Ministry of Health. Population data came from the Department of Informatics of the Unified Health System. Microsoft Office Excel 2010 spreadsheets and Stata software version 11.2 (StataCorp LP, College Station, TX, USA) were used to organize data, calculate indicators and statistical analysis. In Brazil, 6,600,987 maternal deaths were recorded, of which 4095 were related to preeclâmpsia. The highest concentration of maternal deaths from PE in the age group from 20 to 29 years. Preeclâmpsia-related mortality rates showed an upward trend in Brazil and Ceará. The municipalities that had the highest rates of maternal mortality from preeclâmpsia as the underlying cause in Brazil were Itaú (RN), Ruy Barbosa (RN) and Corumbataí (SP) as the underlying cause + associated in Brazil were São José do Peixe (PI), Ruy Barbosa (RN), Corumbataí (SP) and São Gonçalo do Gurgueia (PI). High-risk spatial and spatio temporal clusters were identified for preeclâmpsia-related mortality as the underlying cause and as the underlying + associated cause located mostly in the Northeast. In the state of Ceará, the municipalities of Reriutaba, Lavras da Mangabeira and Tejuçuoca were the ones with the highest mortality rates due to preeclâmpsia as the underlying cause, while the municipalities of Campos Sales, Catunda and Potengi were the ones with the highest rates of mortality due to preeclâmpsia. preeclâmpsia as underlying + associated cause. The municipality of Viçosa do Ceará was identified with a high mortality rate related a preeclampsia. High numbers of deaths from the disease were recorded nationally. The state of Ceará followed the national scenario from the perspective of characterization of deaths.The results presented reveal the need for advances in research on the subject and serve as additional subsidies for monitoring and evaluation that strengthen discussions to qualify the planning and implementation of strategic actions across the country.